(untitled) (Nepal Medical College Journal, 2024)
Nevus lipomatosis cutaneous superficialis (NLCS) is an uncommon benign hamartomatous condition characterized by mature ectopic adipocytes in the dermis. Here we present a case of a 34 years female with a four years history of multiple, skin coloured, painless nodules over the inner side of the right upper thigh. The lesion was excised and sent for histopathological examination and was found to be nevus lipomatosis cutaneous superficialis. Such a case is rare and only few cases have been reported in context of Nepal hence the recognition of the condition is important.